HUBUNGAN KEPUASAN PETANI DALAM USAHATANI SAYURAN DENGAN KINERJA PENYULUH PERTANIAN DI KECAMATAN POASIA KOTA KENDARI - Yuda Dwi Atmaja; Dasmin Sidu; Putu Arimbawa (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The agricultural sector, particularly the horticultural industry in Southeast Sulawesi, plays a pivotal role in economic development and job creation. However, in the Poasia Subdistrict, the potential for vegetable cultivation has not been optimized due to low production and limited extension support, access to inputs, and extension workers whose performance does not fully meet farmers' needs. The objective of this study is to ascertain the correlation between the level of satisfaction among farmers engaged in vegetable farming and the effectiveness of agricultural extension workers in Poasia District. The research population consists of vegetable farmers in Poasia District who are spread across various subdistricts, with a total of 53 people. The research sample was obtained through the implementation of a census or saturated sampling method. The data collection techniques employed included interviews, documentation, and surveys. The results of the study show that the level of farmer satisfaction in vegetable farming in Poasia Subdistrict has a strong relationship (0.660) with the performance of agricultural extension workers. Farmer satisfaction is seen from the factors of production input, production output, marketing, and the performance of agricultural extension workers. In general, the level of satisfaction is in the moderate category. Farmers are most satisfied with the use of pesticides (73.58%) and fertilizers (62.26%), while the land aspect shows the lowest level of satisfaction (11.32%) due to limited cultivation area. In terms of production output, 66.03% of farmers were satisfied with the previous year's output, but only 26.41% were satisfied with the current year's output due to weather factors and limited inputs. In terms of marketing, ease of market access and price stability increased farmer satisfaction to 66.03%. Meanwhile, the performance of agricultural extension workers was rated as good, especially in terms of clarity of material (62.26%) and extension methods (73.58%), which contributed positively to increasing farmer capacity.